Language Disorders in Stuttering Behavior During Childhood Development / الاضطرابات اللغوية في سلوك التأتأة أثناء نمو الطفولة - R. Taufiqurrochman; Yusti Dwi Nurwendah (Abjadia, 2019)
Language is a communication system that cannot  separated from any human life. A person's language skills  filled with various aspects that interrelated with each other, such as aspects of health, environment, intelligence, and other elements. However, someone who is interrupted by his speech function will also experience issues of his language. This study written to describe the form of expression experienced by stutterers, what factors influence stuttering behavior, and the influence of stuttering behavior on the process of communication with others. This study uses a qualitative approach to analytical methods. First, the researcher listens to the stutterers, conducts interviews, examines the data, and then analyzes it. Based results analysis, it  found stuttering language experienced subject study occurred in all the sentences came out of his speech. His stuttering behavior has caused by environmental factors where he experiences constant fear, which then impacts his speech function in the long term. Because of his stuttering behavior, his communication with others was limited and very disturbed.اللغة هي نظام الاتصال لا يمكن فصلها عن أي حياة بشرية ما. يتم المهارات اللغوية الشخصية بجوانب متنوعة مترابطة ببعضها البعض كجوانب الصحة والبيئة والاستخبارات والجوانب الأخرى. فإن الشخص الذي يضطرب من خلال وظيفته في التحدث سيختبر أيضًا من جوانب لغته. تمت كتابة هذه الدراسة بهدف وصف شكل اللغة التي يواجه المتلعثمون، ما العوامل التي تؤثر على سلوك التأتأة، وتأثير السلوك المتعثر على عملية التواصل مع الآخرين. استخدمت هذه الدراسة نهجًا كيفيا بدراسة الحالة مع أساليب تحليلية. أولاً، استمع الباحثان إلى المتلعثم، ويقومان بإجراء المقابلات، ويفحصان البيانات ثم يحللانها. استناداً إلى نتائج التحليل، وجد أن اللغة المتعثرة التي خاضها موضوع هذه الدراسة وقعت في جميع الجمل التي خرجت من خطابه. ويتسبب سلوكه المتلعثم بعوامل بيئية حيث يعاني من خوف دائم مما يؤثر على وظيفته في الكلام والخطاب. بسبب تصرفاته المتعثرة، كان تواصله مع الآخرين محدودًا ومزعجًا للغاية